А SORAFENIB INDUCED MODEL OF GLOMERULAR KIDNEY DISEASE - STAVNIICHUK, A.; SAVCHUK, O.; HYE KHAN, Abdul; JANKIEWICZ, Wojciech K.; IMIG, John D. (Bulletin of Taras Shevchenko National University of Kyiv. Biology, 2025)
Glomerular damage and proteinuria are important pathophysiological signs of chronic kidney disease. This study provides data obtained using a model developed based on the use of the anti-cancer drug sorafenib. Sorafenib is a tyrosine kinase inhibitor that acts through the signaling pathway associated with vascular endothelial growth factor and is widely used to treat various types of cancer. Sorafenib, on the other hand, causes serious side effects in patients, including the development of chronic kidney disease. This study was aimed at using the nephrotoxic properties of sorafenib to model chronic kidney disease in rats. We showed that rats treated with sorafenib for 8 weeks along with a diet high in salt (8% NaCl) develop hypertension with high systolic blood pressure of 80 mmHg, proteinuria with an increase in protein content of 75% higher , and a 4-fold increase in glomerular damage compared to the control group. In case of damage to the renal glomeruli caused by sorafenib, the level of transcripts that are involved in the synthesis of key glomerular proteins such as nephrine, podocin, synaptopodin and subplanin is significantly reduced. Also, when studying this model, activation of the endothelial-mesenchymal transition is observed. In the group of rats treated with sorafenib, the mRNA level for the WT-1 endothelial cell marker was reduced by 20%, while the concentration of the Col III, FSP-1, α-SMA and vimentin mesenchymal cell markers increased by 2–3 times. Thus, we developed a preclinical model of chronic kidney disease, expressed in damage to the renal glomeruli. We also demonstrated that glomerular damage in this model is associated with decreased expression of key structural glomerular proteins and activation of the endothelial-mesenchymal transition of the kidneys.
Keywords: sorafenib, vascular endothelial growth factor, glomerular injury